In-cylinder heat transfer characteristics of hydrogen fueled engine: a steady state approach - Rahman, Md. Mustafizur; Hamada, Khalaf I; Noor, M.M; Bakar, Rosli A.; Kadirgama, K.; Maleque, Md. Abdul (Science Publications, 2010)
Abstract: This study presents in-cylinder heat transfer characteristics of a single cylinder port injection Hydrogen fueled Internal Combustion Engine (H2ICE) using a steady state approach. Problem statement: The differences in characteristics between hydrogen and hydrocarbon fuels are led to the difference in the behavior of physical processes during engine cycle. One of these processes is the in-cylinder heat transfer. Approach: One dimensional gas dynamic model was used to describe the heat transfer characteristics of the engine. The engine speed was varied from 2000-5000 rpm, crank angle from -40° to +100°, while Air-Fuel Ratio (AFR) was changed from stoichiometric to lean limit. Results: The simulated results showed higher heat transfer rate but lower heat transfer to total fuel energy ratio with increasing the engine speed. The in-cylinder pressure and temperature were increased with decreasing AFR and increasing engine speed. The in-cylinder air flow rate was increased linearly with increasing engine speed as well as air fuel ratio. Conclusion/Recommendations: The results showed that the AFR has a vital effect on characteristics variation while the engine speed has minor effect. These results can be utilized for the study of combustion rocess, fuel consumption, emission production and engine performance.